Dihydromyricetin reverses MRP2-mediated MDR and enhances anticancer activity induced by oxaliplatin in colorectal cancer cells. Issue 3 (March 2017) - Wang, Ziyuan; Sun, Xiaoting; Feng, Yuanyuan; Liu, Xuan; Zhou, Lihong; Sui, Hua; Ji, Qing; E, Qiukai; Chen, Jia; Wu, Lili; Li, Qi
Abstract : Dihydromyricetin (DMY), extracted from the Chinese herbal medicine Ampelopsis grossedentata, possesses antitumor potential in different types of human cancer cells. Hence, its effects on drug resistance and molecular mechanisms in colorectal cancer (CRC) are still unknown. In our present study, we observed that DMY enhanced the chemosensitivity to oxaliplatin (OXA). DMY increased OXA-induced apoptosis and reduced 5(6)-carboxy-2′, 7′-dichlorofluorescein accumulation in OXA-resistant CRC HCT116/L-OHP cells. Our mechanistic study suggested that DMY treatment inhibited multidrug resistance protein 2 (MRP2) expression levels and promoter activity, indicating that DMY reduced not only MRP2 transcriptional and translational levels but also its function. Additional experiments indicated that the nuclear translocation of nuclear factor-erythroid 2 p45 related factor 2, a MRP2 regulator, was also inhibited by DMY. In summary, our study provided the first direct evidence that the inhibitory effects of DMY on MRP2 expression in OXA-resistant CRC cells were closely associated with the inhibition of nuclear factor-erythroid 2 p45 related factor 2 signaling. DMY could be a potential candidate for CRC chemotherapy.